Pseudorabies Virus US3 Protein Inhibits IFN-β Production by Interacting With IRF3 to Block Its Activation - Xie, Jingying; Zhang, Xiangbo; Chen, Lei; Bi, Yingjie; Idris, Adi; Xu, Shujuan; Li, Xiangrong; Zhang, Yong; Feng, Ruofei (Frontiers in Microbiology, 2021)
Pseudorabies virus is a swine alphaherpesvirus, causes neurological disorders and reproductive failure in pigs. It is capable of avoiding host antiviral response. However, the mechanism by which many PRV proteins assist the virus to evade innate immunity is poorly understood. This study identified PRV US3 protein as an extremely important antagonistic viral factor that suppresses interferon beta (IFN-β) expression. A detailed analysis showed that US3 protein inhibited type I IFN production by targeting interferon regulatory factor 3 (IRF3), a key molecule required for type I IFN induction. Additionally, US3 protein interacted with IRF3, degraded its protein expression to block the phosphorylation of IRF3. These findings suggested a new strategy evolved by PRV to inhibit IFN-β production and escape the host innate immunity.